Fluoride mediated conversion of FeOOH into NiFeOOH for outstanding oxygen evolution reaction. (20th February 2022) - Kathale, Benjamin Mulwa; Xiao, Hengbo; Yang, Shengxiong; Yin, Hongxia; Yu, Tianshui; Zhou, Xiangji; Qian, Lihua; Xiao, Junwu; Lei, Pengxiang; Li, Xiuhong
Highlights: Fluoride-doped NiFe catalysts have superb OER performance. Fluorine introduces defects on the NiFe catalyst, subject to its concentration. Defects change the chemical structure, hence influencing the OER performance. Presence of NiF2 phase, mediates FeOOH to NiFeOOH phases in the catalyst. F anions influence the concentration of Ni and Fe cations on the NiFe-catalyst. Abstract: By the use of different concentrations of F, we modulate the structure of NiFe catalysts to have a hybrid structure composed of different phases involved in Oxygen Evolution Reaction (OER) process. For the first time, in-situ Raman spectroscopy was used to study the structural change of the NiFe catalyst, associated with the effects of the concentration of F during the OER process. At a moderate concentration of F, it was found that; (1) the catalysts have a well-conductive hybrid structure composed of NiFeOOH (474 cm −1 and 544 cm −1 ), FeOOH (715 cm −1 ) and NiF2 (310 cm −1 ) phases, and (2) F promotes an optimum mass ratio between Ni and Fe, which helps in the collaborative operation between Ni and Fe. This led to generation of catalysts with an optimum structure portraying excellent OER performance. Specifically, the synthesized catalysts required explicit low overpotential of 259 mV to generate current density of 100 mAcm −2, Tafel slope of 60.3 mVdec −1, high charge transfer rate signified by low resistance of 1.46 Ω, and high number of active OER sites implied by large double layer capacitance of 2.90 mF. This study shades light to the understanding of the involved vital phases of F-NiFe catalysts and how F mediates the active phases during the OER process, hence contributing to the knowledge required for the designing of better catalysts for future electrodes. Graphical abstract: Image, graphical abstract